Probing the catalytic activity of pristine and doped Pd and Ni metal clusters towards H2O molecule - Samal, Pragnya Paramita; Joshi, Krati; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2019)
Electrolysis of H2O to produce molecular hydrogen, the most environment friendly and energy efficient fuel, using cost effective catalysts is one of the major global research challenges. To date, Pt remains the best suitable and yet highly expensive electro-catalyst for hydrogen evolution reaction. Design of an alternative cost-effective catalyst requires a fundamental molecular level understanding of the water molecule adsorption and its activation. In that context, we examine the adsorption and activation of water molecule on model alternative catalysts namely, Ni-6 and Pd-6 clusters using density functional theory based methodology. Ni-6 and Pd-6 clusters and their singly doped counterparts are used for this study. Mo, W, Fe, Co and Cu are used as doping elements. To quantify the influence of medium (neutral and alkaline) on the activation of the water molecule, Ni based clusters are considered in neutral and anionic states, respectively. The activity of these clusters towards H2O molecule is evaluated in terms of the adsorption energy, charge transfer, bandgap, red shift in O-H stretching frequency and dissociation barriers for H2O. The studies demonstrate that doping with Co in all the studied clusters (Pd-6, Ni-6 and anionic Ni-6) increases their activity. Best activity is noted for Fe doped neutral Ni b clusters with a dissociation barrier of 5.76 kcal/mol.
Keywords: Activation barrier; Ni clusters; O-H activation; Pd clusters; Red shift of O-H stretching frequency; Water adsorption

Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

Enhanced photocatalytic properties of a chemically modified blue phosphorene - Maibam, Ashakiran; Das, Sawan Kumar; Samal, Pragnya Paramita; Krishnamurty, Sailaja (RSC Advances, 2021)
It is high time to placate the peak demand for an efficient, economic and green fuel in the form of H-2 through photocatalytic water splitting. Several low dimensional materials have been explored for their photocatalytic properties on account of their surface to volume ratio. The present study illustrates the excellent photocatalytic potential of a two-dimensional material, viz. a chemically tempered blue-phosphorene sheet, with single atom thickness and high carrier mobility. Metal-free element, sulphur, is explored as a dopant in a 32-atom blue-phosphorene sheet. The dopant is inserted at three locations viz. central, edge and central edge positions with varying concentrations from 3.125% to 18.75% (corresponding to n = 1 to 6 sulphur atoms within a 32-atom blue-phosphorene sheet, P32-nSn). The cohesive energy studies predict the higher stability of even number S doped sheets as compared to their odd counterparts. Photocatalytic activity is studied in terms of band gap and band alignment for different concentrations of the former. Studies reveal that edge doping demonstrates better water molecule activation independent of S atom concentration. The edge doped systems not only provide the chemical activity to activate water, but also show feasible HER overpotentials of 1.24-1.29 eV at neutral medium. Finally, this work opens up a driving lead of non-corrosive catalysts for water molecule splitting.

An innovative light assisted production of acetic acid from CO2 and methanol: a first photocatalytic approach using a reusable cobalt(ii) molecular hybrid at atmospheric pressure - Saini, Sandhya; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Ray, Anjan; Jain, Suman L. (Green Chemistry, 2021)
Acetic acid is an important commodity chemical that is produced either by fermentation processes, or more commonly, through chemical routes such as methanol carbonylation with CO and H-2, acetaldehyde oxidation, or hydrocarbon oxidation. More recently, methanol hydrocarboxylation with CO2 and H-2 under thermal catalytic conditions has attracted interest. The synthesis of acetic acid from easily available CO2 is of great significance yet rarely reported. The present paper describes the first photocatalytic approach for the synthesis of acetic acid from methanol and CO2 under ambient reaction conditions without using molecular hydrogen. The maximum conversion of methanol achieved is 60% with a selectivity of 81% towards acetic acid using an octa-sulfur bound cobalt phthalocyanine (CoPc/S8) photocatalyst without an additional sacrificial electron donor. Product analysis, controlled experiments and DFT calculations suggest the formation of methylene carbene as a reactive intermediate. The developed methodology represents a potentially exciting approach for synthesizing acetic acid utilizing CO2 in a sustainable manner.

Mechanistic investigations on the catalytic transfer hydrogenation of lignin-derived monomers over Ru catalysts: theoretical and kinetic studies - Khan, Tufeil Sartaj; Singh, Dheerendra; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Dhepe, Paresh Laxmikant (ACS Sustainable Chemistry & Engineering, 2021)
The hydrodeoxygenation (HDO) reaction of oxygenated compounds such as lignin-derived phenolics is well studied using molecular H-2 as a hydrogen source, yet the use of high pressures discourages its use on an industrial scale. As an alternative, the catalytic transfer hydrogenation (CTH) pathway provides in situ hydrogenation species, which reduces the need for the high-pressure infrastructure required when molecular hydrogen is used. Nevertheless, this strategy is scantly studied, and in lieu with this, herein we report the kinetic and mechanistic investigations of the CTH strategy for the HDO of guaiacol, phenol, anisole veratrole, and eugenol to their respective products. For potential commercialization purposes, low loading of metal, milder reaction conditions, and high selectivity toward desired products with a high H/C ratio were considered while designing catalysts (0.5 wt % Ru on SiO2-Al2O3, SiO2, Al2O3-acidic, Al2O3-basic, and Al2O3-neutral) for these reactions. As high as 74% cyclohexanol yield from guaiacol was achieved at 225 degrees C in the presence of isopropyl alcohol (IPA) as the hydrogen source and over the Ru/Al2O3-acidic catalyst reduced at 150 degrees C. A detailed kinetic study is carried out to understand the interaction of the substrate and intermediates with the catalyst and the influence of reaction parameters on the product formation. It was observed that the cisisomer of 2-methoxycyclohexanol rapidly undergoes further conversion than the trans-isomer. The experimental observations are substantiated through density functional theory (DFT) studies on Ru(0001) and guaiacol molecule complexes. DFT studies indicate that the adsorption of the cis-isomer is more exothermic as compared to that of the trans counterpart, and the underlying electronic factors are elucidated using charge density difference and density of states plots.
Keywords: catalytic transfer hydrogenation; Cyclohexanol; DFT; Hydrodeoxygenation; kinetics; lignin monomers; Supported metal catalysts

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Substrate augmented catalytic activity towards NRR: a case study of Li doped Al clusters on defective graphene - Samal, Pragnya Paramita; Poonam; Krishnamurty, Sailaja (2021)
Density Functional Theory (DFT) based methods are applied to examine the potential of lithium doped aluminium clusters consisting of 3-13 atoms for dinitmgen molecule activation in terms of N N bond length, redshift in N N bond stretching frequency, nitrogen interaction energy and frontier molecular orbitals analysis. The present work highlights the role of monovacant C-3 defective graphene as a support in fine tuning the catalytic activity of Li doped Al clusters for reduction of N-2. Fundamental insights to synergic binding of clusters with defective graphene is brought out and its role in enhancing activation of dinitmgen molecule is explained. Supported Aln-1Li clusters with six or more atoms are noted to be more active towards N-2 molecule activation as compared to the clusters without support. Dinitrogen molecule undergoes a maximum bond elongation of 1.56 angstrom corresponding to redshift of 1690 cm(-1) on Al7Li@graphene and Al12Li@graphene. This is maximum value reported in context of activation for N-2 molecule till date.
Keywords: Al clusters; Al12Li; C-3 defective graphene; DFT; Li Doping; N-2 activation; Red-shift

Thermal stability of an endohedrally doped aluminum nanoclusters: a BOMD study - Singh, Chandrodai Pratap; Samal, Pragnya Paramita; Krishnamurty, Sailaja (Theoretical Chemistry Accounts, 2021)
In this article, thermal stability of doped Al-13 nanoclusters has been systematically investigated within the framework of density functional theory (DFT). To explain thermal stability, simulations have been carried out over a temperature range from 300 to 1100 K using Born-Oppenheimer molecular dynamics (BOMD). The atomic displacements have been quantified by calculating delta(rms,) MSD and epsilon(pro.) The thermal stability of different clusters is explained using underlined electronic properties such as HOMO-LUMO, charges and bond length.
Keywords: BOMD; Bond length fluctuations; Endohedral doping; Mean squared ionic displacements (MSD); Nanoclusters; Root mean squared

Free base phthalocyanine coating as a superior corrosion inhibitor for copper surfaces: a combined experimental and theoretical study - Samal, Pragnya Paramita; Dekshinamoorthy, Amuthan; Arunachalam, Shivakami; Vijayaraghavan, Saranyan; Krishnamurty, Sailaja (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2022)
In the quest of novel, eco-benign copper corrosion inhibitors, free base and a set of six metal Phthalocyanine (Pc) coatings (where metal is Zn, Cu, Fe, Co, Ni, Mn) are systematically evaluated for their corrosion inhibition efficiency. The study demonstrates that the free base Phthalocyanine coatings are superior corrosion inhibitors for Cu surface in HCl with a corrosion inhibition efficiency of 88% as compared to its metal counterparts. A detailed and indepth study involving concerted electrochemical polarisation, impedance measurements at various concentrations of HCl assert the superior corrosion inhibition efficiency of free base Pc coatings as compared to its metal counterparts. Underlying factors/interface chemistry contributing to it is brought out using first principle based studies. First principles based computational studies establish that superior corrosion inhibition ability of free base phthalocyanine molecule is attributed to its innate binding ability with copper surface and its better inter-molecular packing. Thus, the theoretical adsorption trends of various studied phthalocyanine molecules while clearly following the experimental corrosion inhibition efficiency trends undermine the importance of contribution of chelating factors for the formation of a stable and efficient corrosion inhibition coating on a surface and that the adhesion/adsorption strength of a molecule correlates directly to its corrosion inhibition efficiency. The experimental observations are further substantiated through FE-SEM, EDAX and XPS studies. The corrosion inhibition efficiency of free base phthalocyanine is followed by its zinc based counterpart at 85%.
Keywords: Copper surface; Corrosion inhibitors; DFT studies; Impedance; Phthalocyanine coatings

Lewis acid-catalyzed chemodivergent and regiospecific reaction of phenols with quaternary peroxyoxindoles - Shaikh, Moseen A.; Samal, Pragnya Paramita; Ubale, Akash S.; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2022)
The indium-catalyzed regiospecific coupling of substituted phenol derivatives and quaternary peroxyoxindoles for the synthesis of C2 or C4 benzoxazin-3-one-substituted phenols via skeletal rearrangement is described. This reaction is demonstrated with 17 examples with good yields and diverse aryl substituents. In contrast to the indium-catalyzed reaction, the Cu(OTf)2- catalyzed reaction of the phenol with quaternary peroxyoxindoles afforded C2 or C4 2-oxindole-substituted phenol derivatives. This diverse catalytic reaction generated various biologically important phenol-substituted 2-oxindole derivatives directly without any skeleton rearrangement and was demonstrated with 19 examples in high yield. The regiospecificity and the reaction pathways were explained with the support of density functional theory (DFT).

Can Li atoms anchored on boron- and nitrogen-doped graphene catalyze dinitrogen molecules to ammonia? a DFT study - Verma, Tushar Singh; Samal, Pragnya Paramita; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (ChemPhysChem, 2023)
The most successful electrochemical conversion of ammonia from dinitrogen molecule reported to date is through a Li mediated mechanism. In the framework of the above fact and that Li anchored graphene is an experimentally feasible system, the present work is a computational experiment to identify the potential of Li anchored graphene as a catalyst for N-2 to NH3 conversion as a function of (a) minimum number of Li atoms needed for anchoring on graphene sheets and (b) the role of chemical modification of graphene surfaces. The studies bring forth an understanding that Li anchored graphene sheets are potential catalysts for ammonia conversion with preferential adsorption of N-2 through end-on configuration on Li atoms anchored on doped and pristine graphene surfaces. This mode of adsorption being characteristic of Nitrogen Reduction Reaction (NRR) through enzymatic pathway, examination of the same followed by analysis of electronic properties demonstrates that tri-Li atoms (Tri Atom Catalysts, TACs) are more efficient as catalysts for NRR as compared to two Li atoms (Di Atom Catalysts, DACs). Either way, the rate determining step was found to be *NH2 ->*NH3 step (mixed pathway) with Delta G(max)=1.02 eV and *NH2-*NH3 ->*NH2 step (enzymatic pathway) with Delta G(max)=1.11 eV for 1B doped TAC and DAC on graphene sheet, respectively. Consequently, this work identifies the viability of Li anchored graphene based 2-D sheets as hetero-atom catalyst for NRR.
Keywords: computational chemistry; Graphene Sheet; heterogeneous catalysis; Li Nanoparticles; Nitrogen Reduction Reaction

Catalyst-assisted selective vinylation and methylallylation of a quaternary carbon center using tert-butyl acetate - Mohanta, Nirmala; Samal, Pragnya Paramita; Pandey, Akanksha M.; Mondal, Shankhajit; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2023)
The In-(OTf)(3)-catalyzed & alpha;-vinylationof varioushydroxy-functionalized quaternary carbon centers using in situ generatedisobutylene from tert-butyl acetate is presentedas a novel synthetic methodology. Moreover, tert-butylacetate is a nonflammable feed stock and is a readily available sourcefor the in situ production of vinyl substituents, as demonstratedby the vinylation reaction with quaternary hydroxy/methoxy compounds.Moreover, an excellent selectivity for methylallylation over vinylationwas obtained with Ni-(OTf)(2) as a catalyst. In the case ofperoxyoxindole, methylallyl-functionalized 1,4-benzoxazin-3-one derivativeswere formed through the sequential rearrangement of peroxyoxindolefollowed by the nucleophilic attack by isobutylene. The detailed mechanismfor this reaction and rationalization for the selectivity are providedusing kinetics and density functional theory studies.

Expounding lemonal terpenoids as corrosion inhibitors for copper using DFT based calculations - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
The most important bottleneck in identifying an innovative and yet viable corrosion inhibitor for copper surfaces is discerning the chemical interactions at the interface of adsorbate and adsorbent. The present work, primarily, discerns the interface chemistry of green corrosion inhibitors, viz., lemonal terpenoids, with the copper surfaces for the first time. The interface chemistry is evaluated for distinct facets of copper, modelled by periodic surfaces to finite sized aggregates, with two stereoisomers viz., citral and neral through density functional calculations. The adsorption/ interaction properties between the surface and the corrosion inhibiting molecule are analysed through the electronic properties such as density of states, charge density difference plots and Bader charges where in distinct bonding mechanisms are identified as a function of varying facets. Apart from the adsorption properties, molecular packing properties are of paramount importance towards the design of an efficient corrosion inhibitor for a surface. Hence, we also analyse the intermolecular stacking energies between the inhibitors when packed among themselves in vacuum and when adhered on to metal surfaces. The studies bring forth an understanding that lemon terpenoids are highly potential corrosion inhibitors for copper surfaces, particularly, for Cu (110) surfaces both in neutral and protonated form.
Keywords: Copper surface; Density Functional Theory (DFT); Green corrosion inhibitors; Interface chemistry; Lemonal terpenoids; Molecular stacking

Iron-catalyzed regioselective C-H alkylation of indoles: an additive-free approach in renewable solvent - Pradhan, Chandini; Jagtap, Rahul A.; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Green Chemistry, 2023)
Alkylated indoles are important motifs in various biologically active molecules and drug candidates. Herein, we report a mild and efficient iron-catalyzed protocol for synthesizing alkylated indoles via C-H bond alkylation of indoles with unactivated alkenes, demonstrating a high level of regioselectivity. The reaction occurs under additive-free, solvent-free (or trace green solvent, 2-MeTHF) and less energy-intensive conditions using a sustainable metal catalyst and provides easy access to privileged alkylated indoles with anti-Markovnikov selectivity. Alkylation is compatible with important functionalities, such as fluoro, chloro, trifluoromethyl, alkenyl, ether, thioether, silyl, and siloxane, including heteroaryl, pyridinyl, carbazolyl, and indolyl moieties (45 examples, up to 96% yield). The developed protocol is very simple, straightforward, and fully accords with the principles of green chemistry. A detailed mechanistic investigation manifests the facile indole's C-H activation at the Fe(0) center, reversible 1,2-insertion of the alkene into the Fe-H bond of a metallacycle, and a turnover-limiting reductive elimination. Alkylated indoles are important motifs in various biologically active molecules and drug candidates.
Keywords: Aromatic Ketones; Green; organic synthesis

MnXWO4 nanostructure-based catalysts for single-step oxidation of cyclohexane and methane to oxygenates - Prabu, Marimuthu; Manikandan, Marimuthu; Samal, Pragnya Paramita; Gurrala, Lakshmi Prasad; Mekala, Siva Prasad; Archana, Ramakrishnan; Nayak, Chandrani; Bhattacharyya, D.; Jha, S. N.; Krishnamurty, Sailaja; Raja, Thirumalaiswamy (ACS Applied Nano Materials, 2023)
Activation of the C-H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on MnxWO4 nanostructures within 6 h. The recyclability test confirmed the catalyst heterogeneity, which revealed no appreciable loss of catalytic activity even after three consecutive reactions. In situ DRIFT study reveals that CYH is oxidized to cyclohexanone and cyclohexanol (KA oil) and is further oxidized to AA via carboxylate intermediates. DFT studies disclosed that MnOx species are responsible for the C-H activation of CYH, and the Mn2+/Mn3+ redox centers play a vital role in the absorption of KA oil to form AA. Herein, we demonstrated the significant role of the ``MnOx'' species and that adequate Lewis and Bronsted acidic sites, redox centers of (Mn2+/Mn3+), and lattice oxygen are accountable for the CYH conversion toward the AA. Additionally, we have reported the oxidation of methane to methanol (146 mu mole per gram of catalyst) in the presence of water at 75 degrees C without over-oxidation products.
Keywords: Adipic Acid; C-H bond activation; Cyclohexane oxidation; methane activation; MnOx chain; Redox center

Sulfonated zinc phthalocyanine coating as an efficient and ecofriendly corrosion inhibitor for copper surfaces: an in silico led design and its experimental validation - Dekshinamoorthy, Amuthan; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Khatri, Praveen K.; Jain, Suman Lata; Ray, Anjan; Vijayaraghavan, Saranyan (Langmuir, 2023)
The current study highlights the successful integration of an in silico design with experimental validation to create a highly effective corrosion inhibitor for copper (Cu) surfaces. The synthesized sulfonated zinc phthalocyanine (Zn-Pc) is electrochemically characterized and demonstrates an impressive 97% inhibition efficiency, comparable to the widely used industrial corrosion inhibitor, BTA, for Cu surfaces. The corrosion inhibition is comprehensively analyzed through potentiodynamic polarization and impedance spectroscopy techniques, supported by their respective equivalent circuits. Furthermore, the sample undergoes thorough characterization using scanning electron microscopy, energy-dispersive X-ray analysis, X-ray photoelectron spectroscopy, contact angle measurements, and atomic force microscopy. Density functional theory calculations reveal that sulfonated Zn-Pc exhibits the highest interaction energy, underscoring its exceptional inhibition properties. These results open possibilities for utilizing computational methods to design and optimize corrosion inhibitors for protection of Cu surfaces.

Breaking the Pt electron symmetry and OH spillover towards ptir active center for performance modulation in direct ammonia fuel cell - Barik, Sidharth; Kharabe, Geeta Pandurang; Samal, Pragnya Paramita; Urkude, Rajashri R.; Kumar, Sachin; Yoyakki, Athira; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2024)
The growing interest in low-temperature direct ammonia fuel cells (DAFCs) arises from the utilization of a carbon-neutral ammonia source; however, DAFCs encounter significant electrode overpotentials due to the substantial energy barrier of the *NH2 to *NH dehydrogenation, compounded by the facile deactivation by *N on the Pt surface. In this work, a unique catalyst, Pt4Ir@AlOOH/NGr i.e., Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles controllably decorated on the pseudo-boehmite phase of AlOOH-supported nitrogen-doped reduced graphene (AlOOH/NGr) composite, synthesized via the polyol reduction method. The detailed studies on the structural and electronic properties of the catalyst by XAS and VB-XPS reveal the possible electronic modulations. The optimized Pt4Ir/ANGr composition exhibits a significantly improved onset potential and mass activity for AOR. The DFT study confirms the OHad species spillover by AlOOH and Pt4Ir (100) facilitates the conversion of the *NH2 to *NH with minimal energy barriers. Finally, testing of DAFC at the system level using a membrane electrode assembly (MEA) with Pt4Ir/ANGr as the anode catalyst, demonstrating the suitability of the catalyst for its practical applications. This study thus uncovers the potential of the Pt4Ir catalyst in synergy with ANGr, largely addressing the challenges in hydrogen transportation, storage, and safety within DAFCs. In this article, a versatile catalyst, Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles decorated on AlOOH/NGr composite. The AlOOH provides an -OH-rich surface conducive to the facile adsorption and decoration of the PtIr alloy nanoparticles and OHad species spillover from AlOOH to the Pt4Ir active center during AOR, further validating the higher experimental activity obtained in Pt4Ir/ANGr. image
Keywords: ammonia oxidation reaction (AOR); d-band center; density functional theory (DFT) study; direct ammonia fuel cells; hydroxyl spillover effect; XAS analysis

First-principles simulation of active site selectivity for CO2 and H2 adsorption on Mg(OH)+/Mg2+ and Ca(OH)+/Ca2+ zeolites - Samal, Pragnya Paramita; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2024)
One very effective strategy for addressing global warming and transitioning to sustainable energy sources is selective CO2 separation over H-2. Porous materials, particularly zeolites, have demonstrated enormous potential for energy-efficient separation techniques combined with storage. By altering interactions at cation-binding sites, zeolite's gas adsorption characteristics toward carbon capture can be improved. In this study, Mg and Ca are assessed as extra-framework cations in divalent (Ca2+, Mg2+) and monovalent states (Ca(OH)(+), Mg(OH)(+)) in faujasite and chabazite zeolites for CO2 capture over H-2. The study also explores the impact of mixed cations, viz., a combination of both Ca2+ and Mg2+ in the framework, on their selective adsorption potential. This study uses DFT with dispersion corrections to calculate adsorption energies, enthalpies, and Gibb's free energies of adsorbed CO2 and H-2 molecules. Among the dispersion parameters evaluated, viz., D4, TS/HI, and MBD, D4 approaches experimental accuracy. In general, the adsorption trend obtained for CO2 is Mg FAU > Ca FAU > Mg CHA > Ca CHA > Mg(OH)(+) FAU > Ca(OH)(+) FAU > Mg(OH)(+) CHA > Ca(OH)(+) CHA. The heats of adsorption using PBE+D4 for CO2 are -46 kJ/mol for Ca FAU and -10 kJ/mol for Ca(OH)(+) FAU, respectively. These values closely align with the experimental results of -45 and -6 kJ/mol, respectively, within a chemical accuracy limit of +/- 4 kJ/mol. The relative adsorption energies suggest that for both FAU and CHA, there exists a minimum difference of 26 kJ/mol in adsorption energies between CO2 and H-2. Hence, this piece of work highlights that FAU with Ca and Mg as extra-framework cations in a six-membered cage can be a viable substitute to replace, the current best candidate in literature, viz., Li+, for selective CO2 capture.

Indazole-5-amine (AIA) as competing corrosion coating to Benzotriazole (BTAH) at the interface of Cu: A DFT and BOMD case study - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Tiwari, Shivani; Shah, Vaishali; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2024)
This study compares three organic compounds-benzotriazole (BTAH), imidazole (IM), and indazole-5-amine (AIA)-as corrosion inhibitors for copper substrates. Using Density Functional Theory (DFT) and Born-Oppenheimer Molecular Dynamics (BOMD) calculations, it identifies AIA as a promising and cost-effective alternative to the toxic BTAH. The adsorption strength on Cu(1 0 0) surfaces is ranked AIA>BTAH>IM for both neutral and deprotonated forms. These findings are supported by electronic parameter studies, including Bader charge analysis, density of states (DOS), charge density differences (CDD), and frontier molecular orbital analysis. AIA shows the best adsorption in a parallel orientation at the top site. Packing studies reveal that hydrogen bonding stabilizes the interaction energies within self-assembled AIA aggregates. Organometallic complexation studies reveal that deprotonated BTAH exhibits higher interaction energy with a single Cu atom compared to AIA when bonded through the carbon end, consistent with the findings from BOMD studies. However, on periodic Cu surfaces, AIA outperforms BTAH molecules as seen from adsorption energies. This investigation highlights AIA's potential as a superior and more economical corrosion inhibitor for copper.
Keywords: Adsorption; Born-Oppenheimer molecular dynamics; Corrosion inhibition; Density functional theory; Indazole derivatives

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter

Synergistic combination of ZnCl2/Cu-BTC MOF for the photocatalytic oxidative deamination of benzylamines using CO2 under visible-light irradiation - Kumar, Amod; Bhatt, Sakshi; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Jain, Suman L. (ACS Applied Engineering Materials, 2024)
This paper demonstrates the first CO2-mediated oxidative deamination of benzylamines to benzaldehydes using a combination of ZnCl2 and Cu-BTC MOF as photocatalysts in a carbon tetrachloride solvent under visible-light irradiation. Interestingly, the synergistic combination of ZnCl2 and Cu-BTC afforded the targeted oxidation of benzylamine to benzaldehyde, wherein CO2 acted as an oxidant. The individual components yielded the corresponding imine as the main product, resulting from the oxidative coupling of the benzylamine. DFT calculations and computational studies supported the proposed reaction pathways involving the formation of an intermediate imine from benzylamine via dehydrogenation followed by hydrolysis to produce benzaldehyde. This work, demonstrating the use of CO2 as an oxidant, may open up new avenues for CO2 utilization in chemical production by using sustainable light energy.

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones

syn-Selective hydrosilylation and hydroboration of alkynes at room temperature catalyzed by a phosphine-free (NNN)Fe(ii) complex - Pradhan, Chandini; Dubey, Shivansh; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Catalysis Science & Technology, 2025)
Catalytic hydrofunctionalization of alkynes is the ideal and atom-economical route to synthesize vinylsilanes and vinylboronates, which are valuable organic building blocks. However, the process suffers from using expensive phosphine-ligated catalysts, sensitive organometallic activators, and elevated reaction temperatures. To overcome these challenges, herein, we developed a series of phosphine-free (NNN)-ligated iron complexes and demonstrated their potential as efficient catalysts for the hydrosilylation and hydroboration of both internal and terminal alkynes using NaOtBu as an activator. The reactions proceeded smoothly using 1.5 mol% catalyst loading at room temperature and provided syn-selective vinylsilanes and vinylboronates. This hydrofunctionalization exclusively delivered mono-silylated and mono-borylated vinyls with tolerance of sensitive functionalities. At the same time, terminal alkynes provided excellent anti-Markovnikov selectivity with thermodynamically feasible beta-(E)-vinylsilanes and beta-(E)-vinylboronates. The presence of an N-H moiety in the ligand backbone is crucial in generating an Fe(ii) active catalyst and facilitating the catalytic process. Mechanistic investigations, including controlled reactions and external additive experiments, were performed to propose a redox-neutral reaction mechanism with iron maintaining its +2 oxidation state throughout the cycle. The DFT energy calculations unanimously support the proposed reaction mechanism.

CO2, N2 and H2 adsorption in Zn2+-containing zeolites and metal-organic frameworks - Samal, Pragnya Paramita; Berger, Fabian; Krishnamurty, Sailaja; Sauer, Joachim (Physical Chemistry Chemical Physics, 2026)
We employ a chemically accurate (+/- 4 kJ mol-1) embedding approach to calculate enthalpies for CO2, N2, and H2 adsorption in the Zn2+-containing zeolites FAU and CHA, and for CO2 and H2 in the metal-organic frameworks (MOFs) Zn-MOF-74 and CALF-20. Using MP2 as the high-level method and PBE+D4 as the periodic low-level method (MP2:PBE+D4), we obtain CO2 adsorption enthalpies of -46, -34, and -36 kJ mol-1 for Zn-CHA, Zn-MOF-74, and CALF-20, respectively, all within chemical accuracy limits of the experimental values of -42, -30, and -39 kJ mol-1. For CO2 in Zn-FAU, where no experimental data exist, we provide an MP2:PBE+D4 prediction of -49 kJ mol-1. For N2, we predict MP2:PBE+D4 adsorption enthalpies of -41 and -39 kJ mol-1 in Zn-CHA and Zn-FAU, respectively. CO2 adsorption is stronger in the zeolites than in the studied MOFs. Across all systems, CO2 adsorption tends to be stronger than N2 adsorption and both are largely favoured over H2. We observe inconsistent accuracy of PBE+D4 for the two MOFs, despite their similar characteristics, underscoring the need for high-level approaches in predictive screening. Additionally, we conclude that Zn2+ cations with open coordination sites act as the primary binding sites and that these cations preferentially occupy 6-membered rings in zeolites.

Silico imine-based ligand engineering of CALF-20 for electrocatalytic ammonia production - Samudre, Nikhil S.; Samal, Pragnya Paramita; Krishnamurty, Sailaja (ACS Sustainable Chemistry & Engineering, 2026)
Electrocatalytic ammonia synthesis is emerging as a globally compelling, sustainable alternative to the Haber-Bosch process under ambient conditions. As a result, active-site engineering has taken center stage in the development of stable and effective electrocatalysts. In this work, we report how the introduction of an imine group in the ligand backbone of CALF-20, a Zn-based, moisture-stable MOF with high surface area, results in the formation of an N-4 macrocycle for transition-metal anchoring. PBE + D3 calculations, supported by spectroscopic, ab initio molecular dynamics, and electronic analyses, identify Fe-bound modified CALF-20 as the most stable configuration among the Mn-, Fe-, Co-, Ni-, Cu-, Ru-, Rh-, Ag-, and Au-anchored within the modified CALF-20 framework. Upon modification, the d-band center shifts from -5.08 to -4.44 eV in M-Fe-CALF-20. Adsorption studies confirm activation of both N-2 and NO2, reflected by bond elongation and red-shifted IR peaks. Mechanistic studies show that M-Fe-CALF-20 selectively facilitates NH3 formation, exhibiting PDS values of 0.69 and 0.62 eV for the NRR and NO2RR, respectively, while a competitive adsorption shows a clear preference over HER. Our study illustrates how functionalization tunes CALF-20 for dual application as an adsorbent and as an electrocatalyst for NH3 synthesis and storage.
Keywords: Adsorption; CALF-20 MOF; electrocatalysis; hydrogen evolution reaction; nitrogen oxide reductionreaction (NO2RR); nitrogen reductionreaction